Brightly shining : a novel - Rishøi, Ingvild H. (Grove Press, 2024)
"Beautifully told with humor and tenderness, a Norwegian Christmas tale of sisterhood, financial hardship, and far-off dreams, acclaimed by reviewers and beloved by readers across Europe, where it has been a bestseller. Christmas is just around the corner, and Ronja and Melissa's dreamer of a father is out of work again. When ten-year-old Ronja hears about a job selling Christmas trees near where the family lives in central Oslo, she thinks it might be the stroke of luck they all need. Soon, the fridge fills with food, and their father returns home with money in his pocket and a smile on his face. But the local pub has an irresistible pull on Ronja and Melissa's father, and before long he disappears into the night under the pretense of buying Christmas gifts. Melissa decides to take his place at the Christmas tree stand, working before and after school, and brings along her sister Ronja, who charms the middle-class customers with her simple sweetness. On rare breaks in the dark of Norwegian December they dream of a brighter place of kindness and plenty, but both girls understand that their family structure is a precarious one. Skillfully told, evoking the delight, misunderstandings, and innocence of a child's voice, Brightly Shining is small in stature but with an outsize impact on the reader, and has all the markings of a magical modern classic"--